Optimal planning and multi-criteria decision making for effective design and performance of hybrid microgrid integrated with energy management strategy. (March 2023) - Bao, Yang; Li, Ruihong; Yang, Xuelan; Saini, Gaurav; Ranjith Krishna, P.; Wang, Genqiang
Highlights: Sustainable hybrid microgrid for community residential loads. Integrated approach combining optimization, energy management, and decision making. Impact of energy management strategy on emission reduction and net present cost. Abstract: The dependence on fossil fuels for energy generation resulted in severe environmental challenges, triggering green transition. As a result, there has been massive uptake of renewable energy share in the energy sector, devising new ways of generating energy. Hybrid microgrids are one such system enabling green transition in the energy sector. However, they mostly face planning and feasibility-related challenges. Such challenges become more complex when consumer's preferences on energy use patterns are considered. Hence, this paper considers designing a hybrid microgrid considering consumer-centric energy management options. A case study has been simulated considering the consumer's preferences on energy use patterns using a hybrid optimization of multiple energy resources tool for understanding the techno-economic-environmental feasibility through which better planning of microgrid infrastructure can be made. The results include the hybrid microgrid system architecture, capacity size optimization, energy performance and cost parameters. The observed energy potential from the optimally planned hybrid microgrid satisfied the electrical energy requirements. It is observed that the energy management option strongly influences the hybrid microgrid system architecture, capacity size optimization, and cost. Based on the observed results, the best-worst method was implemented for decision-making over the system architecture selection considering multiple decisions over techno-economic and environmental aspects.